THE APPLICATION OF THE AUTOSEGMENTAL PHONOLOGICAL THEORY TO THE INDONESIAN REDUPLICATION - Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract. This article analysed reduplication which is viewed from the theory of Autosegmental phonology proposed by John Goldsmith. The basic concept of this theory is that a phonological representation is not the same as that in the generative traditional theory. This theory sees phonological representation as not symply a sequence of segments (each with its properties) but it consists of a string of other elements called autosegments and a specified mapping between them, otherwise it will yield illformed word. The principle in associating fonemic element to the prosodic templete (CV element) is imposed by Marantz as follows: a. consonant links to C slot while vowel links to V slot, association is strictly one-to-one and it starts with melody phoneme. b. CV slot can be prelinked to specific phonemes and pre-association is prior to the autosegmental linking starting from phonemic melody. c. Directions of linking: either the leftmost melody phoneme links with the leftmost appropriate CV slot (for prefix) or the rightmost melody phoneme links with the rightmost appropriate CV slot (for suffix) and linking proceeds towards the root. The result shows that Indonesian reduplications involves affixation and what is affixed to the roots or stems can be the whole CV elements of the root or stem (as illustrated by full reduplications) . or part of the CV elements of the root or stem (as illustrated by partial reduplications)